Pulp revascularization of an immature permanent tooth with apical periodontitis: A case report - Makkar Sameer; Kaler Nisha; Mann Navjot (Serbian Medical Society - Dental Section, Belgrade, 2013)
The present case report analyzes the outcome of revascularization treatment of an immature permanent tooth with necrotic pulp and apical periodontitis. The canal was disinfected with copious irrigation and application of triple antibiotic paste. After the disinfection protocol was completed, apical bleeding was induced in the canal resulting in the formation of a blood clot. An absorbable scaffold was placed over it followed by an adequate triple coronal seal. After nine months follow-up, increased thickening of dentinal walls with intact lamina dura and complete apical closure was reported radiographically. Therefore, revascularization therapy could be recommended as an alternative treatment option.